Hydraulic Impact of Vegetation on the Stability of Shallow Clay Slopes Nature Based Solutions for Mitigation of Erosion in Göta Älv - Margenberg, Maria; Persson, Axel (My University, 2022)
Soil erosion is one of the drivers for landslides in natural slopes. In a climate where both high intensity rain and heavy wind is increasingly common, soil will erode more rapidly, especially in waterways. Traditional erosion barriers, such as rock revels or concrete walls, are not always suitable methods when considering downstream effects and ecological impact. This has led to an increased interest in combined or fully nature-based solutions (NBS). These methods incorporate vegetation to limit soil erosion. The body of the vegetation will reduce the speed of run-off, roots will reinforce the soil and evapotranspiration induces suction in the unsaturated zone, which increases stability. This project consists of a case study and a numerical analysis. The case study investigates four NBS constructed by the Swedish Geotechnical Institute (SGI) in Göta älv. Site visits, soil sampling and discussions regarding NBS for erosion mitigation were undertaken. These barriers attempt to reduce wave energy on riverbanks by different designs, which aims to allow vegetation to take hold. The study found lack of site data and limited time scope to be a hindrance in evaluating the NBS design. Leaning heavily on state of the art literature, suggestions are made to improve the design in future projects. The numerical analyses focused on the hydraulic effects of vegetation in an eroding slope by creating a Finite Element model of natural clay slopes with varying levels of suction and slope angles. This is to compare how failure mechanisms are affected by suction in the topsoil. An exponentially and a parabolic decaying root distribution is compared in a factor of safety analysis which is then related to the evolution of shear bands. The differences in factor of safety were found to be small between the two root distribution geometries, this may be explained by the high water table and small root depth. The analysis show a clear diffusion of slope failure mechanisms as shear bands that are clearly defined without suction are scattered into multiple potential slip surfaces when negative pore pressures are present in the topsoil. These shear bands merge into one band that is generally shorter and shallower than for the bare slope, which has a positive effect on the factor of safety. An increase in factor of safety between 25% and 45%, depending on the amount of suction induced, for a steep slope, is observed. The increase in stability attributable to suction is less prominent at gentle slope angles.
Keywords: sediment transport; landslides; soil suction; slope stability; nature based solutions; NBS; erosion; vegetation; shear bands